Bentuk Penyajian Tari Piring Gelas Di Sanggar Kupek Beghaes Kabupaten Musi Rawas Utara Provinsi Sumatera Selatan - Ayumi, Siska; Riyanti, Eva; Surherni; Syofia, Ninon; Maghfirah, Auliana Mukhti; Ariastuti, Idun (JURNAL ILMIAH NUSANTARA, 2025)
Beghaes Studio, North Musi Rawas Regency, South Sumatra Province. The method used in this study is descriptive qualitative. The purpose of descriptive qualitative methods is to analyze situations or events as they exist, through observation, interviews, and documentation. This study utilizes the presentation form theory proposed by Y. Sumandio Hadi. The results indicate that the presentation form of the Piring Gelas dance is an innovation, based on the Piring Gelas dance, which was once a traditional dance and then transformed into a presentation form. In the Piring Gelas dance, each movement element not only functions aesthetically but also contains symbolic meaning related to the cultural values of the community.